A vida por trás dos galhos das macieiras: (o)posições sociais e representação classista na cadeia produtiva da maçã em Vacaria - RS - Lermen, Nadine Gerhardt (2020)
In the last decades, brazilian agricultural production has been modernized and inserted in the global marketing chains. Among the sectors that have this surplus process are the production of grains and fruits, such as apples. Virtually all Brazilian apple production is carried out in the states of Santa Catarina and Rio Grande do Sul and the largest individual apple producer in the country is the municipality of Vacaria-RS. In this context, the objective of this work is to understand the training process of the apple production chain in Vacaria-RS, with the actors and social actors involved, a constitution of representation of the social classes active in the activity and as the main issues in relation to the capital -work in this context in recent decades. To achieve the proposed objective, take Pierre Bourdieu's theory as a theoretical basis, with its concepts of social space, field, capital, social habits and trajectories, and conduct semi-structured interviews with local union leaders, an analysis of secondary data, such as those produced by IBGE, and the content of the main local newspaper and collective work conventions carried out between 1994 and 2019. From the data analyzed, we found that local apple production started in the 1970s, as a result of a political dispute, and the apple production chain consolidated over the following decades, with the concentration of activity among large local companies. With the continued growth in apple production and productivity, there was also a significant increase in the number of temporary and permanent rural wage workers to carry out the aplles production. The representation of these rural classe has been made, mainly, by the Rural Workers Union and by the Rural Union of Vacaria. In view of the asymmetry of power between the employers and the workers, there were differences in the form of organization of these unions. In the Rural Workers Union, leaders have shown greater professionalization, political-union training, paid positions and longer terms. In the Rural Union, managers have high turnover and do not have paid positions or union training. Among the main activities developed by both unions is the negotiation of collective labor agreements, which are held annually. In these negotiations, wage readjustments and working conditions for rural workers in the municipality are defined and it is at this moment that the real clash between capital and labor occurs. In the case of rural workers in Vacaria, despite the advances achieved by the Rural Workers Union in collective agreements, the employers' sector has managed to maintain a large part of the clauses that favor rural landowners, ensuring the maintenance of established social positions, what was corroborated by the approval of the new labor legislation in 2017.